Toward Agentic HRD: A Translational Model of Albert Bandura's Human Agency Theory. Issue 3 (August 2019) - Yoon, Hyung Joon
The Problem: Albert Bandura has refined a theory of human agency with three modes and four core properties within social cognitive theory. Human agency plays a critical role in one's adaptation, self-development, and self-renewal. Despite its relevance to human resource development (HRD), human agency theory has not been explored or effectively utilized in HRD research and practice. The Solution: Following Bandura's human agency theory, a translational and implementational model for HRD was proposed. First, the model integrated the four core properties of human agency (intentionality, forethought, self-reactiveness, and self-reflectiveness) into a model by altering the sequence to align with major HRD processes. Second, it synthesized triadic reciprocal determinism with the four core properties of human agency by placing the agent at the center of the model. Third, it is an open systems model that describes reciprocal determinism between the agent and the environment at micro, meso, and macro levels, indicating the dynamics of personal, proxy, and collective agency. The Stakeholders: The model will be useful for career practitioners, coaches, organization development consultants, and other HRD professionals who deliver interventions. HRD researchers and theorists may find it worthwhile to test and validate the model. In addition, regardless of disciplines, researchers, and practitioners who follow social cognitive theory may find some insights from the translational model.